PERCEPTION OF THE PUBLIC TOWARD SHARIA PAWNING (RAHN) PRODUCTS AS A FINANCIAL ALTERNATIVE - 'Aliyah, Aghnat (Ar-Rihlah : Jurnal Keuangan dan Perbankan Syariah, 2026)
ABSTRACTThis study aims to analyze public perception of Islamic pawn (rahn) products as a financial alternative. The research employs a quantitative approach, with surveys as the primary data collection instrument. The findings reveal that the public perceives Islamic pawn products as a fair and Sharia-compliant solution, especially for those with limited access to conventional financial institutions. Key factors influencing acceptance include public understanding of the rahn concept, trust in Islamic institutions, and operational transparency. This study aims to provide recommendations for Islamic financial institutions to enhance public literacy and trust in rahn as part of financial inclusion. Keywords: Islamic Pawn, Rahn, Public Perception, Financial Alternative, Financial Inclusion